2020
DOI: 10.31557/apjcp.2020.21.7.2013
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus Detection and Abnormal Anal Cytology in HIV-infected Patients Using p16/Ki-67 Dual-Staining

Abstract: Objective: We investigated human papillomavirus (HPV) infection and detected anal squamous intraepithelial lesions by modified liquid-based cytology (LBC) and p16/Ki67 dual-staining. Methods: Anal swabs (n=393) were collected from patients with HIV infection. Anal cells were kept in 95% ethyl alcohol for modified LBC. DNA was extracted from cells for HPV detection and genotyping using real-time PCR and reverse line blot hybridization. Results: Nine samples (2.3%) were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…For all the biomarkers, we observed that, in HIV-infected MSM, the positivity rate increased significantly with the grade of the cytological alterations, consistently with previous studies [ 21 , 25 , 26 ] and a recent meta-analysis [ 4 ]. Differently, we did not observe this trend in HIV-uninfected MSM, probably due to the limited number of samples evaluated for this subgroup.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…For all the biomarkers, we observed that, in HIV-infected MSM, the positivity rate increased significantly with the grade of the cytological alterations, consistently with previous studies [ 21 , 25 , 26 ] and a recent meta-analysis [ 4 ]. Differently, we did not observe this trend in HIV-uninfected MSM, probably due to the limited number of samples evaluated for this subgroup.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, the cytological categories showed different predictive values in the identification of histological HSILs [ 16 ]. In order to improve the detection of these lesions and to use more objective methods, several HPV-related biomarkers have been evaluated, mainly in HIV-infected MSM [ 17 , 18 , 19 , 20 , 21 , 22 ]. High-risk (hr)HPV E6/E7 mRNA (thereafter hrHPV mRNA) has gained attention because it indicates an active and transforming HPV infection.…”
Section: Introductionmentioning
confidence: 99%
“…Some have focused on anal biopsies 14,15 while others on anal cytology. [16][17][18][19][20][21] High correlation between dual staining on anal cytology specimens and HR-HPV detection has been shown, 17 with high sensitivity for dual staining for AIN3 though low specificity on subsequent biopsy. 18 However, another group found low sensitivity and specificity for dual staining for the detection of biopsy proven HSIL, concluding that p16/Ki67 immunostaining did not improve the diagnostic accuracy of anal cytology.…”
Section: Discussionmentioning
confidence: 99%
“…The P16 protein is the first tumor suppressor gene found at human chromosome 9p21, which is directly involved in the regulation of cell cycle [40]. P16 is an important molecular marker for HPV infection into cervical cells, and could accumulate in cells, which could be clearly detected by IHC [41][42][43]. Previous studies have shown that the tumor suppressor gene P16 was overexpressed in 99% of hr-HPV positive cervical cancer and precancerous lesions, therefore, P16 protein can be used as a biomarker for early screening of cervical cancer and precancerous lesions [44].…”
Section: Discussionmentioning
confidence: 99%